Nanotechnology-based Drug Delivery Systems as Potential for Skin Application: A Review - Baveloni, Franciele Garcia [UNESP] (2021)
Administration of substances through the skin represents a promising alternative, in relation to other drug administration routes, due to its large body surface area, in order to offer ideal and multiple sites for drug administration. In addition, the administration of drugs through the skin avoids the first-pass metabolism, allowing an increase in the bioavailability of drugs, as well as reducing their side effects. However, the stratum corneum (SC) comprises the main barrier of protection against external agents, mainly due to its structure, composition and physicochemical properties, becoming the main limitation for the administration of substances through the skin. In view of the above, pharmaceutical technology has allowed the development of multiple drug delivery systems (DDS), which include liquid crystals (LC), cubosomes, liposomes, polymeric nanoparticles (PNP), nanoemulsions (NE), as well as cyclodextrins (CD) and dendrimers (DND). It appears that the DDS circumvents the problems of drug absorption through the SC layer of the skin, ensuring the release of the drug, as well as optimizing the therapeutic effect locally. This review aims to highlight the DDS that include LC, cubosomes, lipid systems, PNP, as well as CD and DND, to optimize topical skin therapies.